Thermal characteristics of tribovoltaic dynamic Schottky junctions - Deng, Shuo (2023)
It has been recently observed that direct current can be generated through sliding a doped semiconductor or metallic electrode against another doped semiconductor due to the tribovoltaic effect. Here, we present a detailed study on how the mechanical to electric power conversion is influenced by temperature in tribovoltaic dynamic copper/silicon (Cu/Si) Schottky junctions. The effects of temperature on the short circuit current and open circuit voltage of tribovoltaic dynamic Cu/Si Schottky junctions are associated with the balance between generation and recombination of carriers. We show that the peak power density of tribovoltaic dynamic Cu/heavily doped p-type Si Schottky junction sharply increase from 19W/m2 at room temperature up to 1300W/m2 at 373K, suggesting that the power output of the junction can be enhanced by thermal assistance. This work not only provide the thermal analysis of tribovoltaic dynamic processes, but also study the strong synergetic enhancement of the mechanical to electric power conversion by thermal process.